Manajemen Pengawasan Mutu Produk PadaUD Kangen Water di Kelurahan Lukluk, Kecamatan Mengwi, Kabupaten Badung - NI MADE DWIYANI CITA ARSANI; I KETUT SUAMBA; IDA AYU LISTIA DEWEI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2016)
Abstract Management Quality Control Product on UD Kangen Water in Kelurahan Lukluk, Kecamatan Mengwi, Kabupaten Badung Supervision and quality control is an important factor for a company to maintain consistency of product quality, because quality is a priority for business activities. It is necessary to control the management and quality control for all production processes. The purpose of this study was to know how the process, quality control management system and quality control costs. The study was conducted on drinking water products Kangen Water. Data used in the study are data on the number of production, the amount of product damage, and control costs in the period January to December 2014. The results showed system management are in a state of control because the the value of the proportion of disability is between the upper limit and a lower limit, which shows the value of control limit ( ) = 2,9%, the upper control limit (UCL) = 4,3%, lower control limits (LCL) = 1,4%. The costs for quality control shows the magnitude of Quality Control Costs (QCC) is Rp 161.373.033,7, Quaity Assurance Costs (QAC) is Rp 8.900.000,00, and Total Quality Costs (TQC) is Rp 170.273.033,7. So the company able to suppress the number of product damage amounting to 445 bottles, or 2,9 % of total production. The optimum value (q*) is 1.894,8. Keywords : Quality control, System Management, Quality Costs